Learning Styles In Differentiated Instructions Are Mistakes: A Literature Study - Muhammad Sobirin (PT PUSTAKA CENDEKIA GROUP, 2024)
Differentiated learning aims to accommodate students' diverse needs, abilities, and preferences in the educational process. However, the concept of